DEVELOPMENT OF FORENSIC LABORATORIES IN THE FIELD OF DIGITAL FORENSICS IN UZBEKITAN - I. M. Kupriyanova (Web of Journals Publishing, 2025)
This article examines the current state and key areas of forensic laboratory development, focusing on institutional changes, human resources, logistical equipment, the legal environment, and interdepartmental cooperation.
Keywords: Digital forensics, cybercrime, forensic laboratories.